The Physical Work Environment and Sleep: A Latent Class Analysis. Issue 12 (December 2019) - Magee, Christopher; Gopaldasani, Vinod; Bakand, Shahnaz; Coman, Robyn
Abstract : Objective: To investigate the relationships between the physical work environment and sleep using a person-centered approach. Methods: A total of 542 Australian employees aged 18 to 60 years completed a survey assessing exposure to physical work environment stressors (eg, noise, poor air quality, and hazardous manual tasks), sleep timing and sleep quality, and relevant covariates. Results: Latent class analysis (LCA) revealed three physical work environment classes: Infrequent exposure (51%); Occasional Exposure (31%); and Regular Exposure (18%). LCA also identified four sleep classes: Larks (24%); Typical sleep (43%); Insufficient sleep (20%); and Owls (13%). The Regular Exposure class was significantly associated with the Insufficient Sleep (odds ratio [OR] = 3.15, [1.29, 7.66]) and Owls (OR = 3.47 [1.24, 9.71]) classes. Conclusions: The person-centered approach provides important insights into how unique physical work environment experiences are linked with sleep.